Studi In Vivo Efek Nefroprotektif Ekstrak Etanol Batang Tali Kuning (Anamirta cocculus (L.) Wight & Arn.) terhadap Profil Kreatinin Serum Mencit - Dian Nur Khofifah; A. M. Muslihin; Lukman Hardia (Journal of Pharmaceutical and Sciences, 2026)
Background: Nephrotoxicity due to the use of drugs such as gentamicin can cause kidney damage characterized by increased creatinine levels. The use of medicinal plants as nephroprotective agents is a potential alternative; one such plant is yellow rope stem (Anamirta cocculus (L.) Wight & Arn.), known to contain antioxidant compounds. Objective: This study aims to assess the nephroprotective activity of yellow rope stem ethanol extract and determine the optimal dose for reducing gentamicin-induced increases in creatinine levels in mice. Method: The study was conducted experimentally with a pre-test and post-test design using the maceration method with 70% ethanol solvent. Mice were divided into six groups, namely negative control, positive control (vitamin E), healthy control, and three treatment groups with varying extract doses. Creatinine levels were measured using the Jaffe method with a UV-Vis spectrophotometer. Results: The results showed that the yellow rope stem ethanol extract at a dose of 77 mg/kgBW was able to reduce creatinine levels significantly (p<0.05), while lower doses did not show a significant difference. Conclusion: Ethanol extract of yellow rope stems has nephroprotective activity at an optimal dose of 77 mg/kgBW, thus having the potential to be developed as a herbal agent to protect kidney function.